Crafting tradition : the making and marketing of Oaxacan wood carvings / Michael Chibnik. - Chibnik, Michael, 1946- (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2003)
Since the Mid-1980S, whimsical, brightly colored wood carvings from the Mexican state of Oaxaca have found their way into gift shops and private homes across the United States and Europe, as Western consumers seek to connect with the authenticity and tradition represented by indigenous folk arts. Ironically, however, the Oaxacan wood carvings are not a traditional folk art. Invented in the mid-twentieth century by non-Indian Mexican artisans for the tourist market, their appeal flows as much from intercultural miscommunication as from their intrinsic artistic merit. In this beautifully illustrated book, Michael Chibnik offers the first in-depth look at the international trade in Oaxacan wood carvings, including their history, production, marketing, and cultural representations. Drawing on interviews he conducted in the carving communities and among wholesalers, retailers, and consumers, he follows the entire production and consumption cycle, from the harvesting of copal wood to the final purchase of the finished piece. Along the way, he describes how and why this "invented tradition" has been promoted as a "Zapotec Indian" craft and explores its similarities with other local crafts with longer histories. He also fully discusses the effects on local communities of participating in the global market, concluding that the trade in Oaxacan wood carvings is an almost paradigmatic case study of globalization.